Reforming Online Teaching of ’Font Design’: Integrating Ideological Perspectives to Enhance Cognitive and Team Dynamics in Sports Education - Chuqiao Cui; Leiyin Chen (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Font design involves the creative arrangement and re-creation of text, aligning with font style standards and design principles to achieve both aesthetic appeal and effective knowledge dissemination. Beyond shaping the visual beauty of characters, font design also fosters a deeper connection to emotional and psychological expression, making it a critical component in art and design education. Teachers are tasked with developing not only technical skills but also cultivating students' capacity to use font design as a medium for cognitive and emotional engagement. In the context of sports education, font design gains additional relevance by serving as a tool for enhancing communication, team dynamics, and psychological well-being. Integrating ideological and political education into the font design curriculum can provide a more holistic teaching framework. By reforming the curriculum to meet evolving educational objectives and student needs, this approach bridges technical proficiency with critical thinking and emotional development. These reforms are essential not only for advancing the font design discipline but also for equipping students with the psychological and collaborative skills needed in sports environments, where effective communication and aesthetic engagement play vital roles in fostering team cohesion and individual growth. Keywords: Font Design, Ideological and Political Courses, Online Teaching, Teaching Reform.